(untitled) (Fiep Bulletin - online, 2015)
In the today’s society it’s possible to see, larger intensities from the discussions that deal with the getting old process of the human being.Based in that discussion, it points out the elderly person presence, and by extension the subjects of the quality of life that is supposed, been deep-rooted to his or her existence.However, in the study we intend to open another dimension in the debate about the subject, where the explanation of what we may understand as quality of life can be focus.For, besides that, considering the longevity on the people, checked specially in the last thirty years in the Brazilian context, stands as very important, trying to know if the human being, living at the getting old stages, searches for quality of life or life with quality, that way it seems interesting to show the many topics about the matter according to what is really possible to be understood referring to the quality of life aspects, connected to the human being, relating to what is known about his or her existential universe, and so, about the whole period of life being covered by quality.